2014
DOI: 10.1093/humrep/det465
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor promotes the development of human ovarian early follicles during growth in vitro

Abstract: This work was supported by the National Basic Research Program of China (2011|CB944504, 2011CB944503) and the National Natural Science Foundation of China (81200470, 81000275, 31230047, 8110197). There are no conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 54 publications
2
37
0
3
Order By: Relevance
“…5). These current findings are consistent with the results of a previous study that showed that HGF and bFGF promoted cell proliferation and delayed oocyte aging during culture in vitro [30, 31]. …”
Section: Discussionsupporting
confidence: 93%
“…5). These current findings are consistent with the results of a previous study that showed that HGF and bFGF promoted cell proliferation and delayed oocyte aging during culture in vitro [30, 31]. …”
Section: Discussionsupporting
confidence: 93%
“…We developed an encapsulated in vitro follicle growth (eIVFG) culture system, which preserves 3D follicular structure with paracrine signaling maintained between oocyte, granulosa and theca cells (Kreeger et al, 2006;Tingen et al, 2011;Tagler et al, 2012;Hornick et al, 2013). In addition to murine follicles, success to date in the culture of larger mammalian species has been reported in the alginate system including follicles from dog, rhesus macaque, goat, baboon and human (Xu et al, 2009a(Xu et al, ,b, 2010(Xu et al, , 2011b(Xu et al, ,c, 2013aSongsasen et al, 2011;Camboni et al, 2013;Fisher et al, 2013;Araujo et al, 2014;Silva et al, 2014;Wang et al, 2014). Further, eIVFG has facilitated studies of inter-and intra-follicular mechanisms governing follicularphase processes including antrum formation, oocyte maturation and granulosa cell proliferation (Kreeger et al, 2006;West-Farrell et al, 2009;Hornick et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrated that a 3D culture technique utilizing alginate hydrogel (a system previously developed by others) [11, 39] sustained the ability of cat secondary and early antral follicles to grow and survive in vitro for up to 15 d. Furthermore, unlike in earlier cat studies [37, 38], some of the resident oocytes (up to 21%) recovered from donor follicles cultured in the 3D alginate system retained the capacity to resume meiosis and complete nuclear maturation. In that context, this alternative mode of incubation itself imparted advantages for incubating premature cat follicles, as it has for the mouse [7], human [9, 10, 40] and non-human primate [11, 12]. For the human, secondary follicles exposed to such conditions maintain a normal morphological structure, increase in size, and actually form an antral cavity by the 30 th day of culture [11].…”
Section: Discussionmentioning
confidence: 99%